Pengaruh Waktu Reaksi Pada Sintesis Biodiesel Dari Minyak Jarak Pagar (Jatropha Curcas) Menggunakan Katalis La/Lempung - Muhammad Sulthon Siregar; Syaiful Bahri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Jatropha curcas is used as a raw material for making biodiesel because the oil content of jatropha seeds is quite high around 30-50%. In this study, the transeterification of Jatropha oil into biodiesel has been conducted using La/Clay catalyst. This catalyst is made by clay activated using a NaOH base solution with concentrations 1N, 2N, and 3N and impregnated using metal La 1%, 3%, and 5% w/w. La/Clay catalysts were characterized using SEM-EDX and BET. The catalyst obtained proved has a surface area of 6.37 m2/g. La/Clay catalyst is used as a catalyst in the transesterification reaction with a variation of reaction time (120 minutes, 150 minutes and 180 minutes). Effect of catalyst activation, metal La impregnation, and time of transeterification reaction on biodiesel yield has studied. From the results obtained, the best condition was the activation of clay catalyst activation using NaOH 3N, 5% lanthanum metal impregnation, and 180 minutes of transesterification reaction time, obtained 84,64% biodiesel yield. The produced biodiesel fulfilled SNI 7182:2015 having characteristics: density 884 kg/m3, viscosity 4.08 cSt, acid number 0.46 mg-KOH/g, and flash point 136 °C.Keywords: biodiesel, jatropha curcas oil, la/clay, transesterification, yield